Isolamento de aptâmeros ligantes à sequência 3'-UTR do RNA do vírus da dengue - (:unkn) unknown (Universidade Federal de Goiás, 2015)
Considering potential molecular methods for diagnostic and/or therapeutic purpose of infectious human diseases, such as dengue, highlights the systematic evolution of ligands by exponential enrichment, known as SELEX. In this method, ligands to a target are exponentially enriched generating aptamers of DNA or RNA with high specificity, being considered as artificial antibodies. In this work, we aimed to realize the isolation of aptamers binding to 3'-UTR (untranslated region) of the RNA from dengue virus (DENV), because present important conformational structures that act as functional elements into RNA necessary in the infectious process. Total RNA of C6/36 infected cells was extracted, submitted to reverse transcription reaction to obtain viral cDNA (serotypes 2 and 3) and amplified by symmetric and/or asymmetric PCR technique to produce the 3’-UTR from DENV as target, generating RNA-like by containing deoxyuridine triphosphate (dUTP) and biotin in the 5’ region of the target. The random library of RNA ligands was obtained by sonication of a pool from human genomic DNA used in three successive PCR, and in the last reaction was introduced the promoter of T7 RNA polymerase, presenting fragments ranging from 80 to 600-bp. Eight rounds of selection were performed between the target and the library by using paramagnetic particles coated with streptavidin. For each round, after the incubation, the non-ligands were removed by using magnetic platform, and the ligands were eluted with NaOH. The eluted ligands were precipitated, submitted to RT-PCR and transcription in vitro, completing one round of selection. For analysis of variability of ligands, the product obtained from the eighth round was cloned and fourteen clones were randomly selected for amplification. The results demonstrated that the aptamers presented sizes with estimated molecular weights varying from 80 to 100-bp. These data indicated the viability of aptamers isolation against conformational elements present in the 3'-UTR of RNA from dengue virus, which may contribute to future research focusing on prevention and/or control of the disease.
Isolation of aptamers ligands to 3'-UTR sequence of the RNA from dengue virus
Keywords: SELEX; Ácido ribonucleico; Aedes aegypti; DENV; SELEX; Ribonucleic acid; Aedes aegypti; DENV; CIENCIAS EXATAS E DA TERRA::QUIMICA